The Effect of Mulligan Mobilization Technique in Older Adults with Neck Pain: A Randomized Controlled, Double-Blind Study - Oznur Buyukturan; Buket Buyukturan; Senem Sas; Caner Karartı; İsmail Ceylan (Pain Research and Management)
Background. The purpose of this study was to examine the effect of Mulligan mobilization technique (MMT) on pain, range of motion (ROM), functional level, kinesiophobia, depression, and quality of life (QoL) in older adults with neck pain (NP). Methods. Forty-two older adults with NP were included in the study, and they were randomly divided into two groups: traditional physiotherapy (TP) group and traditional physiotherapy-Mulligan mobilization (TPMM) group. Treatment program was scheduled for 10 sessions. Participants were assessed in terms of pain, ROM, functional level, kinesiophobia, depression, and QoL both pre- and posttreatment. Results. Pain, ROM, functional level, kinesiophobia, depression, and QoL improved in both groups following treatment (p<0.05). When comparing effects of these two treatment programs, it was observed that the TPMM group had a better outcome (p<0.05) in terms of ROM, kinesiophobia, depression, and QoL. Conclusion. In older adults with NP, MMT has been found to have significant effects on pain, ROM, functional level, kinesiophobia, depression, and QoL as long as it is performed by a specialist. “This trial is registered with NCT03507907”.